Hydrogenation and dehydrogenation cycle properties of Ti–Mn based alloy Ti0.93Zr0.07Mn1.15Cr0.35 in hydrogen gas. (26th July 2019) - Noritake, Tatsuo; Aoki, Masakazu
Abstract: Hydrogenation and dehydrogenation cycle tests at 0 °C for Ti0.93 Zr0.07 Mn1.15 Cr0.35 were carried out 2000 cycles and more in the hydrogen gas with purity of 99.99% and 99.99999%. The capacity maintenance rates at the 2000th cycle for the first cycle were 82% and 97% for each purity hydrogen gas, respectively. It was found that the cycle durability of this alloy depends on the gas purity. By the X-ray diffraction and light element analysis, it was confirmed that the C14 type crystal structure of this alloy was maintained but the nitrogen concentration in the sample with large capacity reduction was increased after the cycle test. The main factor of the decrease in capacity of this alloy is degradation due to reaction with impurity gas components such as nitrogen. Highlights: The capacity reduction by the cycle test depends on the hydrogen gas purity. The capacity of the Ti–Mn alloy hardly decreases in high purity hydrogen gas. The C14 type crystal structure of the Ti–Mn alloy is maintained after the test. Nitrogen as an impurity in hydrogen gas increases in this alloy after the test.